Que termine em nós e desate: epistemologia e fabulação a partir da (re)apresentação documental de uma “Bixa Travesty” - Zacariotti, Daniel Jose De Castro Silva (2022)
The present research aims, in view of the recent and incipient occurrence of projects and actions dedicated to trans and transvestite artistic, political, and intellectual production, to carry out an expanded audiovisual analysis of the documentary film “Bixa Travesty”, directed by Claudia Priscilla and Kiko Goifman, which brings the story of the artist Linn da Quebrada in documentary format. For this, we will develop and present the bases of expanded audiovisual analysis through its four research movements, namely: spherical movement, spiral movement, funneled movement, and fabulative movement. These movements will help us to observe both the subjects of this research and the empirical object in a multi-situated way. Thus, this analysis will still take place in an intersectional and interdisciplinary way in order to discuss the knowledge involved in the documentary image of this dissident body of gender, race, and class. In the film “Bixa Travesty” we can see that Linn is, not only the subject of the documentary but also the guide, who leads the path that the film takes and what are the paths and possibilities of (re)presentation of the filmic narrative – this being a reason for being credited as co-writer. We bring to the debate thinking about how Linn da Quebrada's documentary (re)presentation in "Bixa Travesty" creates a space to produce knowledge, affectation, and creation of dissent actions in the distribution of the sensitive and, what are the various intermediaries that surround this film and what are the possibilities of movement it creates in the spectator body. For this, we first discuss the whole sphere that involves “Bixa Travesty” and, after that, we make a fabulative analysis – focusing on the possibilities of reality created from the (re)presentation of Linn's body in the documentary. With this, we believe that the spectator body is impelled to resist the neoliberal ideals that form contemporary society and, at the same time, the transvestite ideal is rethought in the face of the social. We hope that, with this research process, we can not only emphasize the urgency of transvestite occupation but also demarcate transvestite production as a process of fabulation of possible futures.